The Influence of Tic Tac Toe Game towards Students’ Speaking Ability - Rahmania, Nadira (Raden Intan State Islamic University of Lampung, Indonesia, 2024)
This study aims to determine the impact of using the Tic Tac Toe game on students' speaking abilities in the second grade at SMK N 7 Bandar Lampung during the academic year 2023/2024. The researcher wants to know how well the second graders at SMK N 7 Bandar Lampung master their language skills, mainly speaking skills. This study used a quasi-experimental design. The population consisted of second-grade students from SMK N 7 Bandar Lampung. The total sample size was 64 students drawn from two classes, XI Accounting 1 (experimental class) and XI Accounting 2 (control class), using cluster random sampling. The experimental class played tic-tac-toe, while the control class played role-playing games. The data were gathered using pre-and post-tests. The instrument consisted of oral test instruction for the pre-test and post-test, with topics covering asking and giving opinions. To analyze the data, the independent t-test formula from the SPSS 26 version was used in statistical computations. The t-test results reveal a significant impact of the Tic Tac Toe game on students' speaking ability. The generated Sig. (2-tailed) of equal variances assumed is 0.000, which is less than Ha = 0.05, indicating Ha's acceptance. This suggests that the use of the Tic Tac Toe game can significantly enhance the speaking abilities of second-grade students at SMK N 7 Bandar Lampung. These findings have practical implications for language educators, providing a promising tool to improve students' speaking skills